COMPARISON OF COMPANIES’ STOCK RETURNS BETWEEN CONSUMER SECTOR AND CONSTRUCTION SECTOR ON THE INDONESIA STOCK EXCHANGE - Christian, Christian; Rustam, Rinaldi (Jurnal Ekonomi & Studi Pembangunan, 2018)
This research attempts to analyze risk and stock return of consumer sector and construction sector at Indonesian Stock Exchange. This research used the documentation method to collect the data. Data has been taken from Bloomberg Terminal. The sample is four corporations, with two corporations for each sector from 2011 until 2016. This research is using the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) for data analysis. Unfortunately, the Capital Asset Pricing Model (CAPM) has poor overall explanatory power, whereas the Arbitrage Pricing Theory (APT) model allows multiple sources of systematic risks to be taken into account and performs better than the CAPM, but both of the tests are considered. In regression analysis, the dependent variable used in the model is stock return. The result shows that inflation has insignificant effect on stock return. Furthermore, consumer sector has negative and significant effect on stock return. Conversely, construction sector has positive and significant effect on stock return.